An international perspective on contemporary developments in victimology: a festschrift in honor of Marc Groenhuijsen - Joseph, Janice 19XX-; Jergenson, Stacie; Groenhuijsen, M. S. (Springer eBook Collection, 2020)
Part I New Perspectives and Approaches in Victimology -- 1 Cyber Victimology: A New Sub-Discipline of the 21st Century Victimology -- 2. From Victim to Survivor to Overcomer -- 3. The Relevance of Error Margins in The Trend Towards Algorithmic Victimology: Some Remarks on The Futures of Theory and Risk Assessment From The Spanish Periphery -- 4. A Victimological Exploration of the African Values of Ubuntu -- 5. New Perspectives on a General Methodology of Victim Support -- 6. Victim Labeling Theory; A Reappraisal -- Part II: Types of Victimization -- 7. Arab girls at risk of victimization: Cultural and Personal characteristics -- 8. Transphobic Femicide: An Intersectional Perspective -- 9. Maritime Piracy Victimization of Seafarers and Their Families -- 10. Domestic Minor Sex Trafficking in the United States: A Victim-Centered Approach -- 11. Findings from an Intervention on the Prevention of Sexual Abuse of Children from Mayan Communities in Mexico -- Part III: Victims’ Rights and Participation in the Criminal Justice System -- 12. What Can We Achieve By 2030? Rights for Victims of Crime in the Era of Sustainable Development Goals -- 13. The Value of Legal Provisions for An Adequate Treatment of Victims of Crime: Does The Victims’ Rights Directive of The European Union Set A New Benchmark? -- 14. Ensuring Victims’ Participation in the Criminal Justice System of the United States of America -- 15. Improving access to justice: Procedural justice through legal counsel for victims of crime -- 16. Victims Behind the Model Minority Myth: Are Asian Americans Model Victims? -- Part IV: Practical Dimensions of Victimology -- 17. Victim-Initiated Restorative Justice -- 18. Restorative Justice implemented by the Judiciary in Brazil: results and the role of the victim -- 19. Introducing restorative approaches in prison settings: An example of a Victim Awareness Program in Serbia -- 20. Restitution: Helping Victims or Offenders? -- 21. Evaluating the Challenges to Victim Services in North America -- 22. Applied Victimology: The Professional Practice of Victimology.